GABRB3 mutation as a cause of Ohtahara syndrome: A case report (Indian Journal of Case Reports, 2021)
Ohtahara syndrome (OS) is a rare early infantile epileptic encephalopathy that is characterized by an abnormal electroencephalogram (EEG) and intractable seizures. The patient of this reported case is a 4-month-old male infant delivered by cesarean section with an uneventful antenatal and neonatal period. At 2 months of age, he developed seizures that were refractory to anticonvulsants. Prolonged video EEG showed a characteristic suppression-burst pattern. We report an infant OS associated with heterozygous mutation in the GABRB3 gene.